The Combination of R&D and MDLC Models in WEB-Based Interactive Learning Media - Ullya Mega Wahyuni; Jefril Rahmadoni; Afriyanti Dwi Kartika; Hafizah Hanim (Sistemasi: Jurnal Sistem Informasi, 2022)
The Technopreneur is a core course offered in semester IV (four) in the Information Systems department, Faculty of Information Technology, Unand. Based on observations, the learning process using the lecture method via video conference makes students more inclined to be subordinated. At the same time, the lecturer position tends to appear as a one-man show. The problems make students more-passive and weak in the creative power. To attract students' interest in learning, it is necessary to develop interactive learning media. This research aims to produce a WEB-based interactive learning media with a combination of R&D and MDLC model. Learning media is designed based result course learning process on the previous semester and user needs. Based on the results of system functionality testing, it shows 100% of the features are functioning properly. While testing user satisfaction on multimedia elements from 20 respondents with the Mean Opinion Score (MOS) scheme was obtained at 4.11, which means the learning media is quite good. For interactive elements, it gets a score of 4.31, which means it is included in the category ready to be applied in the Technopreneur class.